The education of the future - Christensen, John Cornelius (My University, 1894)
Introduction: Education has passed through a process of evaluation following the general advancement of civilization. As the ideas of the people have changed, changes have been brought about in education. Every age has fostered some favorite idea, the ruling motive of the time, but this has in its turn passed away to give place to new ideas. Education, in the different periods of history, has had for its aim the attainment of the favorite idea of that age. The idea of Greece was beauty, and her culture was directed towards that end. The Roman idea was martial valor, and the training of the youth of that country was for the formation of the soldier.
Citation: Christensen, John Cornelius. The education of the future. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Education; Soldier; Culture; Future; Theses; Manuscripts (documents)